Protocol to identify flavonoid antagonists of the SARS-CoV-2 main protease - Moua Yang; Lin Lin; Robert Flaumenhaft (STAR Protocols, 2024)
Summary: Flavonoids are naturally occurring metabolites of plants that can inhibit the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) main protease (Mpro), which is required for viral replication. Here, we present a protocol to identify flavonoid antagonists of the SARS-CoV-2 Mpro. We describe steps for the expression and purification of Mpro and a kinetic enzymatic assay for Mpro activity using a dequenching fluorescence resonance energy transfer peptide substrate. We then detail procedures for using this enzymatic assay to test flavonoid antagonism and reversible inhibition.For complete details on the use and execution of this protocol, please refer to Lin et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.